1996
DOI: 10.1007/bf02790145
|View full text |Cite
|
Sign up to set email alerts
|

Selenium, zinc, and thyroid hormones in healthy subjects

Abstract: Iodothyronine 5' deiodinase, which is mainly responsible for peripheral T3 production, has recently been demonstrated to be a selenium (Se)-containing enzyme. The structure of nuclear thyroid hormone receptors contains Zinc (Zn) ions, crucial for the functional properties of the protein. In the elderly, reduced peripheral conversion of T4 to T3 with a lower T3/T4 ratio and overt hypothyroidism are frequently observed. We measured serum Se and RBC GSH-Px (as indices of Se status), circulating and RBC Zinc (as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(16 citation statements)
references
References 23 publications
0
15
1
Order By: Relevance
“…Although an altered metabolism of TH due to low Se status has been proposed as a mechanism for the age-dependent changes in TFTs [ 7 , 8 ], extensive profiling of thyroid parameters in the current study did not reveal any association of TFTs with Se status. Our analysis included assessment of T3/T4 and T3/rT3 ratios as a reflection of the peripheral metabolism of TH.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Although an altered metabolism of TH due to low Se status has been proposed as a mechanism for the age-dependent changes in TFTs [ 7 , 8 ], extensive profiling of thyroid parameters in the current study did not reveal any association of TFTs with Se status. Our analysis included assessment of T3/T4 and T3/rT3 ratios as a reflection of the peripheral metabolism of TH.…”
Section: Discussioncontrasting
confidence: 75%
“…Peripheral metabolism of TH levels is predominantly mediated by the selenoenzymes type 1, type 2, and type 3 deiodinase (D1-3), which all contain a selenocysteine in their catalytic centre. An altered metabolism of TH due to low Se status has been proposed as a mechanism for the age-dependent changes in thyroid parameters [ 1 , 7 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mean plasma selenium concentration of our elderly participants (1.20 lmol/L) was higher than in an earlier cohort of older New Zealand women (0.90 lmol/L) (14), a 1977 study of older adults (0.48 lmol/L) (34), and New Zealand adults (1.14 lmol/L) (10). We had expected the selenium status of our older adults to be lower than that of younger adults, as shown in several studies (27,34,35), a likely result of low micronutrient intake in older adults (36,37). The higher than expected selenium status of our older participants reflects the trend of increasing selenium status among New Zealand residents (8,38).…”
Section: Discussionmentioning
confidence: 89%
“…Kvícala et al (1995) reported significant relationships over a range of measures of Se status and thyroid hormone parameters (T 4 and T 3 :T 4 ) in 380 Czech inhabitants aged 6-65 years, but not always in all of the narrower age ranges. Olivieri et al (1996) reported a highly significant positive correlation between the T 3 :T 4 ratio and indices of Se status in healthy elderly Italian subjects with marginal Se status, concluding that reduced peripheral conversion of T 4 is related to inadequate Se status in the elderly. Se supplementation resulted in a reduction of T 4 but no changes in the T 3 :T 4 ratio (Olivieri et al 1995).…”
Section: Discussionmentioning
confidence: 93%
“…Although our blood Se concentrations may not be in the range in which effects on thyroid function have been observed, the combination of low Se status and mild I deficiency may be significant. A number of human studies have shown alterations in the T 3 :T 4 ratio associated with low Se and I status (Kvícala et al 1995;Olivieri et al 1996;Ravaglia et al 2000). Therefore, it is important to determine whether there are any detrimental effects of marginal status of Se and I in our population.…”
mentioning
confidence: 99%